Passive versus active cold water immersion post-exercise: Core temperature afterdrop and subsequent exercise performance - Crampton, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Cold water immersion (CWI) is a popular recovery intervention following high-intensity training and competition across a variety of sports. `Afterdrop` is the decrease in core temperature (Tc) occurring after prolonged CWI. This study investigated the magnitude of the afterdrop induced and sprint capacity following active and passive CWI. Methods: Male triathletes (n=8) completed sets of 3 by 30-s Wingate tests (4 min rest interval) on a Lode electromagnetic cycle ergometer pre- and post- randomised 30-min recovery periods. Passive hip-level CWI at 15°C (CW15) was compared with active CWI at 15°C (CW15-EX), active thermoneutral immersion at 34°C (TWI-EX) and active non-immersed control (CON-EX). The active component consisted of seated arm-cranking at 40% Pmax on an adapted Monark cycle ergometer during the immersion phase. At 3 hour pretest volunteers ingested a gastrointestinal sensor (CorTemp); core temperature (Tc) and blood lactate (BLa) data were assessed at regular intervals during exercise and recovery. Data were analysed using two-way repeated measures ANOVA, detected differences quantified using post-hoc Tukey tests (P<0.05) and presented as mean±SEM. Results: Recovery delta Tc (pre- to post-recovery) was significantly greater following CW15 (-0.8±0.2) compared with CW15-EX, TWI-EX and CON-EX (-0.2±0.1; -0.1±0.1; -0.2±0.1°C, respectively; P<0.05). The initial post-immersion afterdrop (delta Tc: end-recovery to start-exercise) was significantly greater following CW15-EX and CW15 (-0.4±0.1; -0.4±0.1) vs. TWI-EX and CON-EX (-0.1±0.1; 0.0±0.0 °C, respectively; P<0.001). Relative BLa post-recovery expressed as % remaining was greater following CW15 (58±2%) vs. CW15-EX, TWI-EX and CON-EX (39±2; 45±3; 39±2%, respectively; P<0.001) inferring reduced lactate clearance. Average mean power normalised to body mass was significantly lower following CW15 (7.3±0.1) vs. CW15-EX, TWI-EX and CON-EX (7.7±0.2; 8.0±0.2; 7.9±0.2 W.kg-1, respectively; P<0.001). In addition, average mean power normalised to body mass was significantly lower following CW15 and CW15-EX (7.3±0.1; 7.7±0.2) compared with pre-recovery data (7.9±0.2; 8.1±0.2 W.kg-1, P<0.05), however, following TWI-EX and CON-EX data were unchanged. Discussion: Arm-cranking exercise (40% Pmax) limited the decrease in Tc during CWI; however, both passive and active CWI resulted in a significant core temperature afterdrop effect post-immersion. Overall BLa clearance during CWI was significantly improved with the addition of low intensity arm exercise. Both passive and active CWI had a negative effect on subsequent sprint performance however this effect was greatest following passive CWI.